Do carbon emissions increase borrowing costs? Evidence from Indonesian SOEs - Selbi, Richa Angelia; Setiawan, Doddy (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2026)
Climate-related risks have become increasingly relevant in corporate financing decisions. Yet, empirical evidence on how carbon emissions affect borrowing costs in state-owned enterprises (SOEs), particularly in developing countries, remains limited. In this study, borrowing costs are proxied by the cost of debt. This study analyzes the effect of carbon dioxide (CO₂) emissions on the cost of debt of Indonesian SOEs listed on the Indonesia Stock Exchange during the 2015–2024 period. Using a quantitative approach, the study employs firm-level data from LSEG Refinitiv and estimates fixed-effects panel-data regressions with clustered standard errors at the firm level. Robustness tests are conducted through winsorization and lagged independent variables. The results show that CO₂ emissions have a positive and significant effect on the cost of debt, indicating that creditors consider environmental risk when setting borrowing costs, even for state-owned firms. This relationship remains consistent in the winsorized specification, although the lagged emission variable is not statistically significant. The findings support the risk-based pricing, signaling, and legitimacy perspectives by showing that carbon emissions function as a relevant financial risk signal in debt markets. This study contributes to the sustainable finance literature by providing evidence from Indonesian SOEs, a context that remains underexplored in prior studies. In practice, the results imply that SOEs need to strengthen carbon-emission management, environmental governance, and transparency in disclosure to maintain more efficient access to debt financing.